Risk Factors for Falls in Patients with Alzheimer Disease: A Retrospective Study of Balance, Cognition, and Visuospatial Ability - Mayuka Oki; Miyuki Matsumoto; Yukiko Yoshikawa; Mitsuko Fukushima; Akira Nagasawa; Tomokazu Takakura; Yukiko Suzuki (Dementia and Geriatric Cognitive Disorders Extra, 2021)
Aim: This study aimed to determine the main risk factors for falls in patients with Alzheimer disease (AD) by comparing balance, cognition, and visuospatial ability between those who have experienced a fall and those who have not. Methods: Forty-seven AD patients were admitted to a ward for patients with dementia (22 men and 25 women). The balance of patients was evaluated using the Functional Reach Test (FRT), the one-leg standing duration, and the Timed Up and Go (TUG) test. The Mini-Mental State Examination-Japanese (MMSE-J) was used to evaluate cognition. For visuospatial ability assessment, the Clock-Drawing Test (CDT) as well as overlapping figure identification and shape discrimination in the Visual Perception Test for Agnosia (VPTA) were used. The patients were allocated to either the fall group or the nonfall group based on their history of falls in the past year. The relationships between patients’ characteristics and evaluation outcomes were compared and examined. Logistic regression analysis was performed using a fall as the objective variable. The area under the curve (AUC) and the cutoff value were calculated. Results: Of the 47 participants, 22 had experienced falls within the past year (46.8%). The results of the FRT, one-leg standing duration, the TUG, the CDT, and the VPTA were significantly lower in the fall group. No significant difference between the MMSE-J scores of the fall group and those of the nonfall group was observed. The results of the logistic regression analysis indicated that falls in AD patients were significantly associated with the FRT. It was found that a shorter FRT distance (cm) had a significant impact on falls. For the FRT, the fall-related AUC was 0.755. At a cutoff value of 24.5 cm, the level of sensitivity was 68.0%, and the level of specificity was 77.3%. Conclusions: The findings of this study indicate that balance and visuospatial abilities are risks factors for falls in AD patients. In contrast, cognitive impairment was not a risk factor for falls. It was demonstrated that the FRT could be an appropriate risk predictor for falls in AD patients. In particular, falls in AD patients were strongly affected by a reduced dynamic balance.